DETERMINATION OF FACTORS CONTRIBUTING TOWARDS CIRCULAR ECONOMY: AN EMPIRICAL EVIDENCE OF HOMEMAKERS – NON WORKING FEMALES. - Ratnesh, Dr. Kumar; Sharma, Dr. Priyank; Singh, Ms. Lata S.P; Goel, Dr. Ankur (The journal of contemporary issues in business and government, 2021)
Purpose- This paper highlighted the significance of various factors influencing the contribution of home economists or simply the homemakers (non working females) towards the ‘Circular Economy’. The study was based on the empirical study conducted in Meerut City in western UP, India. Design/Methodology/Approach- The paper employed the exploratory research design in the initial stage for identifying the influencing factors/variables and furthermore descriptive research design was used to analyse the primary data. The sample unit was the housewives/house makers (non working females) of Meerut City with sample size of 250 (valid responses). Tabulation, Cross Tabulation & Descriptive Statistics were utilized to describe the data and ‘Correlation and Regression techniques’ were used for compiling the results. Findings- The findings ascertained that mostly house makers were in the age bracket of 26-35 years, post graduates with an income level of Rs. 40000/- pm who were significantly contributing towards ‘Circular Economy’. This contribution had positive relationship with various relevant factors, out of which most significant were ‘Resource saving initiatives’, ‘Avoiding Unnecessary use of Social Media’ and Recycling of the Products’. Practical Implication- The study was highly practical being ‘Circular Economy’ had been the most sought transformation in recent times and every social unit was responsible for the same. Homemakers were the key managers in terms of managing the whole house and they required more visibility and transparency for their fruitful efforts towards economy of the nation. Originality/Value- The study was highly valuable because the entire world had been stepping towards the circular economy and the paper was original as it was based on primary data obtained from 250 (valid responses) of housewives of Meerut City.